PERAN GURU DALAM MENCIPTAKAN IKLIM KELAS KONDUSIF UNTUK MENINGKATKAN MOTIVASI BELAJAR DALAM PEMBELAJARAN PAI DI SEKOLAH DASAR - Hisny Fajrussalam; Abdah Birrul Walidain; Faza Zakiyyan; Miana Syifa; Miana Syifa4, Salma Indah Oktriana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
A conducive learning climate can increase student motivation because students will feel comfortable and focus on participating in learning activities. A conducive classroom climate plays an important role in creating student learning motivation in the learning process. The classroom climate will trigger a good learning attitude in students. The big whisper of student learning effort depends on a conducive classroom climate. The purpose of this study was to examine the teacher's role in creating a classroom climate and motivation to learn PAI at SDN Trayu Kulonprogo. This study uses a qualitative method with a case study approach. The research location is at SDN Trayu, Galur District, Kulonprogo. The data source used is primary data, which was conducted through interviews with one PAI teacher as an informant and observation, as well as secondary data, namely related documents. This study uses three techniques in data collection: observation, interviews, and documentation. Data analysis involves three activity streams: data reduction, data presentation, and the formulation of conclusions. The validity of the data in the study was checked using two filtering and data validity checking techniques, namely observation persistence and triangulation, including source triangulation and technique triangulation. The results of the study show that the teacher's role in creating a conducive classroom climate and learning interest in PAI learning at Trayu Elementary School has contributed to supporting the motivation of their learning activities. Learning with various representations will generate student motivation, which leads to a conditional classroom climate for learning.